(untitled) - Koreňová, Katarína (Aura musica, 2013)
The article describes the creation and activities of Female and Mixed Choirs at the Conservatory of Jan Levoslav Bella from different aspects: historical, practical and repertoire and it also shows the achievements and awards of the choirs.
Keywords: choir singing; female choir; mixed choir; students